Payroll Tax Reductions for Minimum Wage Workers: Relative Labor Cost or Cash Windfall Effects? - Sophie Cottet (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper uses administrative employer-employee data to uncover the effects of a large payroll tax reduction for minimum-wage workers in France. Exploiting the change in labor costs both at the job level and at the firm level, I find that the policy spurred an additional 13 percentage points increase in the number of minimum-wage jobs, and that these extra jobs stem exclusively from firms which had previously very few or no minimum-wage workers. On the other hand, firms which already employed workers at minimum-wage levels, and therefore benefit ex ante from a cash windfall, increase employment irrespective of wage levels. These firms grow by an additional 4 percent in the first two years following the reform. This effect is stronger in liquidity-constrained and credit-constrained firms. Overall, these results show that not all firms react to changes in relative labor costs and highlight the importance of alleviating liquidity constraints for firm growth.
Keywords: H22; H25; H32; J21; J23; 330; payroll taxes; firm behaviour; rent sharing; minimum wage